PENGARUH KUALITAS PELAYANAN DAN EMOTIONAL BRANDING TERHADAP KEPUASAN KONSUMEN (Studi Kasus Pasien Rawat Inap Rumah Sakit Umum Permata) - Rizki Ichwan Pradana; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2017)
The development of the economy and society’s needs encourages companies to provide the optimal quality of services they provide. Permata Blora Public Hospital as a company engaged in health service is required to provide optimal service and build a good relationship with consumers. This study aims to determine the effect between service quality and emotional branding on the satisfaction of the inpatients of Permata Blora Public Hospital. This research uses explanatory research method. Sampling technique that used is non probability sampling technique, that is purposive sampling with sample amounted to 97 people. This research uses quantitative analysis techniques. Data analysis using validity test, reliability test, correlation coefficient test, coefficient of determination, simple linear regression, multiple linear regression, t test and F test using IBM SPSS Statistic 22 for Windows. Based on the results of analysis, service quality and emotional branding have an influence to consumer satisfaction. Service quality and emotional branding have influence contribution to consumer satisfaction variable as 42,1% which is service quality have contribution as 38,5% and emotional branding as 21,5%. Service quality together with emotional branding have a significant influence on consumer satisfaction. The conclusion of this research indicates that service quality and emotional branding partially or simultaneously has an influence to the inpatients of Permata Blora Public Hospital satisfaction. Based on these results, the suggestion for Permata Blora Public Hospital is have to improve the service quality and continue to develop the application of emotional branding to maintain patient satisfaction.